2017
DOI: 10.1002/joc.5251
|View full text |Cite
|
Sign up to set email alerts
|

Changes in temporal distribution of precipitation in a Mediterranean area (Tuscany, Italy) 1955–2013

Abstract: This study investigates changes in precipitation regimes in Tuscany (central Italy) over the 1955–2013 period, by using the precipitation concentration index (PCI) and rainfall amount. The PCI is a dimensionless indicator of the temporal concentration of the precipitation. Different statistical methods were applied over the whole period and two independent sub‐periods (1955–1984 and 1985–2013). A p‐value <0.05 was chosen as level of significance for all the statistical tests. Main results, coming from 35 weath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 42 publications
4
18
0
Order By: Relevance
“…The estimated scale factor 1 < s < 2 is an upscaling parameter, which is consistent with the assumption that individual sites are fractal elements of the area (e.g., Diodato et al, 2017b). The estimated relative weighting factors a i (i 1, 2, 3) reflect the characteristics of the three stations (e.g., Bartolini et al, 2018). At the low end of the ARB, Vicarello di Volterra (station S 3 ) has the greatest influence on the areal erosivity because it is located upwind of the western currents that are the bearers of heavy rainfall.…”
Section: (R)usle-based Actual Rainfall Erosivity Datasupporting
confidence: 75%
“…The estimated scale factor 1 < s < 2 is an upscaling parameter, which is consistent with the assumption that individual sites are fractal elements of the area (e.g., Diodato et al, 2017b). The estimated relative weighting factors a i (i 1, 2, 3) reflect the characteristics of the three stations (e.g., Bartolini et al, 2018). At the low end of the ARB, Vicarello di Volterra (station S 3 ) has the greatest influence on the areal erosivity because it is located upwind of the western currents that are the bearers of heavy rainfall.…”
Section: (R)usle-based Actual Rainfall Erosivity Datasupporting
confidence: 75%
“…Brunetti et al (2004) observed that in Italy, as for other Mediterranean areas (Alpert et al, 2002), there is a decrease in the number of days with precipitations, despite an increase in rainfall intensity. This trend was also confirmed by studies carried out in Tuscany region by Bartolini et al (2013Bartolini et al ( , 2018, who analysed temporal and spatial changes in precipitation from 1955 to 2013. The study showed how the effects of climate change are evident and have led to a variation in the rainfall regime in recent decades.…”
Section: Introductionsupporting
confidence: 65%
“…This trend was also confirmed by studies carried out in Tuscany region by Bartolini et al . (2013, 2018), who analysed temporal and spatial changes in precipitation from 1955 to 2013. The study showed how the effects of climate change are evident and have led to a variation in the rainfall regime in recent decades.…”
Section: Introductionmentioning
confidence: 99%
“…on the north-eastern slopes of the Apuan Alps mountain range. The average annual climate was characterized by over 2000 mm rainfall [34], and temperature around 10 °C [35]. Local fir species included silver fir and Douglas fir ( Pseudotsuga menziesii ), however only twigs from silver firs were harvested, and the respective needles used for the tests.…”
Section: Methodsmentioning
confidence: 99%